First century of Hideyo Noguchi’s presence in Peru. - Cruzado, Lizardo (2020)
This year, 2020, we commemorate the 100th Anniversary of the physical presence of Hideyo Noguchi in Peru. He arrived here a century ago in the context of his scientific research about the yellow fever that ravaged the northern area of our country. Such period, very similar to the time we live in nowadays, was a time of epidemic and neglect, of hardship and misfortune of various orders in the social fabric of our country. Therefore, today it is necessary to remember the inspiring image of this physician and great man, not without complexities or errors in his human nature, but endowed with deep convictions, spirit of sacrifice and dedication to the suffering humanity through science. The century of the physical presence of Hideyo Noguchi among us, motivates the sketch of this biographical profile.